Development of thermotolerance in Neurospora crassa by heat shock and other stresses eliciting peroxidase induction. - Kapoor, M (1990)
Hyperthermia, CdCl2, sodium arsenite, and H2O2 led to the rapid appearance of high levels of peroxidase in Neurospora crassa cultures and induced tolerance toward normally lethal temperatures in 60-h-old colonies. Intracellular superoxide dismutase levels did not correlate with the development of thermotolerance.